2011
DOI: 10.3892/etm.2011.297
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity analysis of microsatellites on multiple chromosome regions in dysplasia and squamous cell carcinoma of the esophagus

Abstract: Abstract. The objective of this study was to characterize the molecular events in the carcinogenesis of esophageal squamous cell carcinoma (ESCC) and to identify biomarkers for early detection of the disease. Matched precancerous and cancerous tissues resected from 34 esophageal cancer patients from Chongqing, southern China, were compared to evaluate the extent of loss of heterozygosity (LOH). Sixteen microsatellite markers on chromosome regions 3p, 4p, 5q, 8p, 9p, 9q, 11p, 13q and 17p were used for PCR-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Intriguingly, despite shared genetic changes in paired ESCC and IEN samples, a high degree of private mutation sites showed evidence for genetic heterogeneity, 12,29 which was similar to paired Barrett's and EAC samples. 30,31 In addition, some cases showing high heterogeneity between paired IEN and ESCC samples (3 pairs with <5% SNV overlap) implied the possibility of multifocal lesions in the esophagus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intriguingly, despite shared genetic changes in paired ESCC and IEN samples, a high degree of private mutation sites showed evidence for genetic heterogeneity, 12,29 which was similar to paired Barrett's and EAC samples. 30,31 In addition, some cases showing high heterogeneity between paired IEN and ESCC samples (3 pairs with <5% SNV overlap) implied the possibility of multifocal lesions in the esophagus.…”
Section: Discussionmentioning
confidence: 96%
“…[6][7][8][9] However, most studies of precancerous lesions of ESCC were limited to hotspot genes or the allelic loss of tumor-suppressor genes. [10][11][12] The panoramic genetic architecture of the carcinogenesis process is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other alterations detected in dysplasia include hypermethylation at promoters of tumor suppressor genes ( CDKN2A , CLDN3 , and MT1G ) 93,94 and loss of heterozygosity of microsatellite markers. 9598 Together, these findings indicate that even though IEN and ESCC are histologically distinct, they share many pathogenic genomic abnormalities. These might be used as biomarkers for early detection and risk stratification.…”
Section: Inter- and Intratumor Genomic And Epigenomic Heterogeneitymentioning
confidence: 92%
“…Nucleic acid-based studies of precursors have shown increased allelic loss (pointing to potential tumor suppressor gene inactivation sites) with increasing grade of dysplasia at a wide variety of microsatellite loci (i.e., 3p, 4p, 5q, 8p, 9p, 9q, 10p, 11p, 13q, and 17p) (2427). Mutation studies in esophageal squamous precursors have been limited to TP53 , where missense mutations were evident early in esophageal carcinogenesis (four of 11 samples with dysplasia vs one of three normal epithelia) (28).…”
Section: Histologic and Molecular Characterizationmentioning
confidence: 99%